Hydroxychloroquine in Coronavirus Disease 2019 Patients: What Still Needs to Be Known About the Kinetics. (11th May 2020) - Martin-Blondel, Guillaume; Ruiz, Stéphanie; Murris, Marlène; Faguer, Stanilas; Duhalde, Véronigue; Eyvrard, Frédéric; Izopet, Jacques; Mansuy, Jean-Michel; Rolland, Yves; Delavigne, Karen; Guimbaud, Rosine; Pugnet, Grégory; et al.
Abstract: Different dosage regimens of hydroxychloroquine are used to manage coronavirus disease 2019 (COVID-19) patients, without information on the pharmacokinetics in this population. Blood samples (n = 101) were collected from 57 COVID-19 patients for 7 days, and concentrations were compared with simulated kinetic profiles. Hydroxychloroquine exposure is low and cannot be predicted by other populations.